Efim Ivanovich Smirnov as an Outstanding Theorist and Organizer of Soviet Military Medicine and Civil Healthcare (115th Birth Anniversary) - С. В. Борисевич; Э. А. Яковлев (Вестник войск РХБ защиты)
.